2022
DOI: 10.1177/2473974x221088870
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Surgical Treatment of Obstructive Sleep Apnea

Abstract: Objective Determine risk factors for failure to receive surgical treatment among patients with obstructive sleep apnea. Study Design Population-based observational longitudinal cohort study. Setting Population-based database. Methods Multivariate analysis of 500,792 individuals with obstructive sleep apnea from Optum’s deidentified Clinformatics Data Mart database (2004-2018). Results Black race, increased age, diabetes, atrial fibrillation, obesity, and congestive heart failure were independently associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…27 Some studies also reported racial and ethnic disparities but had varied associations based on the type of study. Two large national database studies from the United States reported a lower likelihood of surgery among Black and Hispanic individuals, 25,28 whereas another single institutional study from the United States observed a higher number of Hispanic patients undergoing surgical treatment for OSA. 24 Some of the studies also reported the impact of comorbidities and symptom severity in treatment type as such, patients with fewer comorbidities had a higher chance of receiving PAPalternative treatments.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Some studies also reported racial and ethnic disparities but had varied associations based on the type of study. Two large national database studies from the United States reported a lower likelihood of surgery among Black and Hispanic individuals, 25,28 whereas another single institutional study from the United States observed a higher number of Hispanic patients undergoing surgical treatment for OSA. 24 Some of the studies also reported the impact of comorbidities and symptom severity in treatment type as such, patients with fewer comorbidities had a higher chance of receiving PAPalternative treatments.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…22,29 Moreover, reduced rates of surgical treatments were reported among patients with Charlson Comorbidity Score >1 or other conditions that elevated anesthesia risks. 24,28 A general lack of awareness regarding alternative OSA treatment options, 30 importance of improving daytime sleepiness 26 as well as partners witnessing nighttime snoring and apnea 31 were also reported as factors influencing individual decision to receive PAP-alternative treatments. Additionally, studies reporting on income noted that OSA patients with higher income and occupational status were more likely to receive PAP-alternative treatments.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%